1976
DOI: 10.1095/biolreprod15.5.654
|View full text |Cite
|
Sign up to set email alerts
|

A Delayed Antagonistic Effect of Progesterone on the Estradiol-Induced Differentiation of the Oviductal Epithelium in Spayed Cats

Abstract: We have shown previously (West et al., 1976) that progesterone (P) antagonizes the effect of estradiol (E2) on the oviducts of cats when E2 and P are administered sequentially (E2 first, then

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, hormones and drugs known to cause shape changes in cultured bone cells (prostaglandins E x and E 2 , PTH, and (B u ) 2 cAMP) have no effect on the degree of tubulin polymerization (35). With regard to reproductive steroid hormones, estrogen is known to promote differentiation of the ciliated oviduct (36)(37)(38), while progesterone antagonizes the effect of estrogen (39). It is not known whether these hormones affect assembly of the ciliary microtubules and/or synthesis of tubulin and the associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hormones and drugs known to cause shape changes in cultured bone cells (prostaglandins E x and E 2 , PTH, and (B u ) 2 cAMP) have no effect on the degree of tubulin polymerization (35). With regard to reproductive steroid hormones, estrogen is known to promote differentiation of the ciliated oviduct (36)(37)(38), while progesterone antagonizes the effect of estrogen (39). It is not known whether these hormones affect assembly of the ciliary microtubules and/or synthesis of tubulin and the associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Results from numerous studies on normally cycling (Brenner, 1969a,b;Verhage et al, 1973a;Odor et al, 19801, ovariectomized (Brenner, 1969a;Brenner et al, 1974;Verhage and Brenner, 1975;Rumery et al, 1978;Pathek et al, 1979;Odor et al, 19801, fetal and prepubertal animals (Allen, 1928;Flerko, 1954;Brenner, 1969a,b;Verhage et al, 1973b) clearly indicate that estradiol (E2) initiates and is required for the development and subsequent maintenance of a fully functional epithelium, i.e., one composed of columnar ciliated and secretory cells. Progesterone (P), on the other hand, antagonizes the growthpromoting effects of E2 and causes the oviductal epithelium to dedifferentiate (Brenner et al, 1974;Verhage and Brenner, 1976;West et al, 1976West et al, , 1977Bareither and Verhage, 1981). As the epithelium regresses there is a loss of cilia and cessation of secretion.…”
mentioning
confidence: 99%
“…Verhage et al (120) noted that plasma E 2 levels were higher during periods of atrophy and deciliation than they were during periods of hypertrophy and reciliation. They concluded that ciliogenesis is a process that is sensitive to low amounts of E 2 and that serum E 2 levels were probably high enough at all stages of the human menstrual cycle to maintain ciliated cells, but that progesterone, when present, was able to block this estrogen effect and require a recovery phase to follow its withdrawal (142). Similar conclusions were reached in studies on cynomolgus monkeys by West and Brenner (123).…”
Section: A Cyclical Changes In Epithelial Morphologymentioning
confidence: 66%